Determinants of intra-industry trade in agricultural and food products between Poland and EU countries - Justyna Łapińska (DANUBE: Law, Economics and Social Issues Review, 2014)
The present study investigates the country-specific determinants of intra-industry trade between Poland and its European Union trading partners in agricultural and food products during the time period 2002-2011. An econometric model for panel data is applied for the analysis of the factors determining Polish bilateral intra-industry trade with European Union countries. The research leads to the formulation of a statement that the intensity of intra-industry trade in agricultural and food products is positively influenced by the intensity of trade with EU countries and the level of economic development of the member countries (as measured by the size of their GDP per capita). Increase in intra-trade turnover is also facilitated by EU membership and by the fact that Poland's trade partners use similar Slavic-based languages. Relative differences in the size of the economies and relative differences in Poland's and its trading partners' levels of economic development have a negative impact. The degree of the imbalance of trade turnover between trading partners also negatively influences the intensity of intra-trade exchange. The research confirms that the impact of all of the identified factors determining intra-industry trade is consistent with the predictions of the theory.
Keywords: 330; Intra-industry trade; Agricultural and food products; Poland; European Union